1999
DOI: 10.1097/00005072-199911000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-1 in Human Alzheimer and Control Brain: Quantitative Analysis of Expression by Microglia and CA3 Hippocampal Neurons

Abstract: Epidemiological and clinical studies suggest that nonsteroidal anti-inflammatory drugs (NSAIDs) that inhibit cyclooxygenase (COX) slow the progression and delay the onset of Alzheimer disease (AD). Two isoforms of cyclooxygenase have been identified. Although much effort has recently been focused on the inducible COX-2 isoform, little is known about COX-1 expression in human brain. We report that COX-1 message and immunoreactivity are localized to human hippocampal CA3 and CA4 neurons, granular neurons in neoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
127
1
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(138 citation statements)
references
References 0 publications
8
127
1
2
Order By: Relevance
“…Studies of neuron-specific conditional knockouts of COX-2 demonstrate that neuronal induction of COX-2 triggers or exacerbates brain inflammation and neurodegeneration after pilocarpine (13). Microglial COX-1 is an alternative source of PGE 2 that might also play a role in brain inflammation (30,31). As brain macrophages, microglia are a major mediator of immune responses in CNS and are effectors of brain inflammation and neurodegeneration in various models of neurological disorders (24).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of neuron-specific conditional knockouts of COX-2 demonstrate that neuronal induction of COX-2 triggers or exacerbates brain inflammation and neurodegeneration after pilocarpine (13). Microglial COX-1 is an alternative source of PGE 2 that might also play a role in brain inflammation (30,31). As brain macrophages, microglia are a major mediator of immune responses in CNS and are effectors of brain inflammation and neurodegeneration in various models of neurological disorders (24).…”
Section: Discussionmentioning
confidence: 99%
“…An increase in COX activity has been reported in the cerebrum of F344 rats at 24 months versus 6 month-old [4], corresponding approximately to the age at which we found increased levels of TXB 2 in this study. Since COX-1 is mainly localized in glia, as opposed to COX-2 which is mainly in neurons [13,50,52], the upregulation of COX-1 could be associated with the aging-related glial activation. In particular, the agerelated increase of GFAP mRNA that we show has been well documented in human and rodent brain [19,29,32].…”
Section: Discussionmentioning
confidence: 99%
“…COX-1 is also up-regulated by retinoic acid during neuronal differentiation of neuroblastoma cell lines (30). Yermakova et al (28) reported a possible relationship between COX-1 expression and Alzheimer's disease. They found COX-1 immunopositive microglia in association with ␤-amyloid plaques, and the density of COX-1 immunopositive microglia in fusiform cortex were increased, indicating the possibility that COX-1 may contribute to central nervous system pathology.…”
Section: Discussionmentioning
confidence: 99%
“…In the brain, COX-2 plays an important role in various pathological conditions (25,26) such as ischemia, seizure, and injury, and has been proposed to contribute to the development of Alzheimer's disease (27,28). On the other hand, the expression of COX-1 is regulated during brain development (29), and COX-1 is also up-regulated by retinoic acid during neuronal differentiation in neuroblastoma cell lines (30).…”
Section: Cyclooxygenase (Cox)mentioning
confidence: 99%